Epigenetics in radiation biology: a new research frontier - Merrifield, Matt; Kovalchuk, Olga (Frontiers in Genetics, 2013)
The number of people that receive exposure to ionizing radiation (IR) via occupational, diagnostic, or treatment related modalities is progressively rising. It is now accepted that the negative consequences of radiation exposure are not isolated to exposed cells or individuals. Exposure to IR can induce genome instability in the germline, and is further associated with transgenerational genomic instability in the offspring of exposed males. The exact molecular mechanisms of transgenerational genome instability have yet to be elucidated, although there is support for it being an epigenetically-induced phenomenon. This review is centered on the long term biological effects associated with IR exposure, mainly focusing on the epigenetic mechanisms (DNA methylation and small RNAs) involved in the molecular etiology of IR-induced genome instability, bystander and transgenerationsl effects. Here, we present evidence that IR-mediated effects are maintained by epigenetic mechanisms, and demonstrate how a novel, male germline specific, small RNA pathway is posited to play a major role in the epigenetic inheritance of genome instability.